Determinant Variables Influencing Patient Intention and Decision Making at Q Dent Smile Dental Clinic - Shella Presilia (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
Q Dent Smile dental clinic is facing difficulties in attracting new patients. To address this issue, the research aims to identify the influence of brand image and firm generated content (FGC) on patient intention, which impacts their decision to choose Q Dent Smile. This study employs the SEM PLS method with a sample of 200 data. The results indicate that FGC positively influences brand image. In addition, brand image and FGC positively influences the patient intention. Brand image also has a direct positive effect on the decision to choose a dental clinic. However, FGC does not directly influence the decision to choose the dental clinic. However, in an indirect test, patient intention significantly mediates the influence of FGC on clinic choice.